KAP STUDY ON CONTRACEPTIVE METHODS IN KANPUR DISTRICT OF UP - Kaushal, S K; Saxena, S C; Srivastava, V K; Gupta, S C; Nigam, S (Indian Journal of Community Health, 2010)
Research question- what is the status of knowledge, attitude andpractices aboutfamilyplanning Objectives: 1. To study the knowledge about various contraceptive, 2. To study the prevalent attitude and practices regarding family planning, 3. To study the influence ofsocialfactors affecting contraceptive use & 4. Tofind out reasons for not adopting contraception. Study design : Cross sectional study Setting and participants: Rural block ofKanpur District and marriedwomen of reproductive age group i.e. 15-49yrs Study period:July to December2005 Sample size : 280 Married women ofreproductive age group i.e. 15-49yrs. Study variable: Knowledge status, attitude, practices, social factors, reasons for not using contraceptives Results : Awareness about contraception was more than 90 percent for all available methods except vasectomy and injectables whiOfi was 31.5% and 8.6% respectively. Only 29.3% of women were currently practicing contraceptive and nearly half (46.42%) had never used. OCP and Condoms qre most commonly accepted methods. Most common reasons observedfor contraceptive defaulter were unavailability (30.88%) and adverse effect (2 6.47%) and for never user need not felt (36.92%) and desire of more children (13.84%). Educational status and joint family structure has positive impact on contraceptive acceptance.